2022
DOI: 10.3389/fpubh.2022.799255
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve the Cognitive Health of Middle-Aged and Elderly People: Evidence From China Family Panel Studies

Abstract: In the context of the rapid development of the internet and the increasing severity of the aging problem, and in order to promote aged health and help construct a healthy society. We use micro survey data from the 2016 China Family Panel Studies (CFPS) to investigate the impact of the internet on the cognitive health of middle-aged and elderly people (those aged 40 and above). The robust results suggest that the internet plays a significant positive role in the cognitive health of middle-aged and elderly peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The finding paralleled that of previous studies proving that adults using the internet for e-mail or online messages had a significantly lower risk of physical limitations. 4 , 28 , 29 , 30 , 31 However, few have investigated whether this effect still holds in a developing context. The present study found the association was more notable and statistically significant in MICs with a higher proportion of digital exclusion, such as China.…”
Section: Discussionmentioning
confidence: 99%
“…The finding paralleled that of previous studies proving that adults using the internet for e-mail or online messages had a significantly lower risk of physical limitations. 4 , 28 , 29 , 30 , 31 However, few have investigated whether this effect still holds in a developing context. The present study found the association was more notable and statistically significant in MICs with a higher proportion of digital exclusion, such as China.…”
Section: Discussionmentioning
confidence: 99%
“…As previous literature has examined that interpersonal relationships and social support are significantly related to Internet addiction ( Yeh et al, 2008 ; Tian et al, 2017 ) and better intergenerational relationships between older adults and their children mean more family support for Chinese older adults ( Li et al, 2019 ). In addition, some studies have confirmed that intergenerational relationships with children affect older adults’ Internet use ( Yuan et al, 2022 ) and social support from family and from a significant other can reduce the older adults’ addictive use of social media ( Özbek and Karaş, 2022 ). Taken together, interactions with children can reduce Internet addiction in older adults while improving their skill to internet use.…”
Section: Discussionmentioning
confidence: 99%
“…As we can see, it is an increasingly common trend for the elderly to be online. However, Internet addiction in older adults is an emerging area, as previous literature has focused more exclusively on the benefits of Internet use in this age group ( Silva et al, 2022 ; Yuan et al, 2022 ). Compared to the youth, the older people have worse health situation and are prone to use Internet excessively due to factors such as physical function and need to supplement social resources through the Internet ( Brailovskaia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, by analyzing data from CFPS conducted in 2016, it was found that internet played a signi cantly positive role in promoting cognitive health of middle-aged and elderly people. Such an effect varied by educational attainments, but not by gender or ruralurban residence [74]. An analysis based on examining Shanghai elders showed that frequent using internet substantially lowered the odds of seniors having mental health problems [75].…”
Section: Internet Use and Individual Healthmentioning
confidence: 97%